Epoxy powder coatings containing polyaniline for enhanced corrosion protection - Radhakrishnan, S.; Sonawane, Narendra; Siju, C. R. (Progress in Organic Coatings, 2009)
Incorporation of polyaniline (PANI) in epoxy type powder coating formulations has not been attempted earlier. Using specific grade of PANI with low doping, it can be incorporated in epoxy powder coating formulations by twin screw extrusion process. The powder formulations were deposited on steel substrates by electrostatic spray coating at -60 W and baked at 140 degrees C for 20 min. These were extensively tested for corrosion resistance by exposure to hot saline conditions followed by electrochemical impedance spectroscopy and also salt spray testing. PANI incorporated coatings showed no deterioration even after 1400 h of hot (65 degrees C) saline treatment. The coatings intentionally scratched also exhibited self healing property and there was no rust formation even after prolonged exposure to hot saline conditions. These results could be explained on the basis of additional crosslinking due to PANI, as confirmed by DSC results, which gave rise to improved barrier property and self healing was associated with the scavenging of ions by PANI which prevented corrosion of the underlying substrate. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Corrosion resistance; Epoxy; polyaniline; Powder coating

Effect of the surface roughness of conducting polypyrrole thin-film electrodes on the electrocatalytic reduction of nitrobenzene - Adhikari, Arindam; Radhakrishnan, S.; Vijayan, M. (Journal of Applied Polymer Science, 2012)
Conducting polypyrrole (PPy) thin-film electrodes were prepared by the electropolymerization of pyrrole on gold-coated glass plates. Films of various roughnesses were obtained by the variation of the scan rates during electropolymerization. These thin films were modified by doping with 6mM of the dopant NiCl2. The surface morphology of the films was studied by scanning electron microscopy and atomic force microscopy (AFM), which suggested films prepared with a high scan rate were rougher in nature than the films produced with a low scan rate. The electrocatalytic reduction of nitrobenzene was carried out with these electrodes with the cyclic voltammetry technique in acetonitrile containing 0.1M HClO4 as a supporting electrolyte. The various results obtained show that the conducting PPy thin-film electrodes were catalytically active toward the electroreduction process. The modified PPy film electrodes doped with NiCl2 were more active toward nitrobenzene electroreduction than the PPy film alone. The results indicate that the roughness of the films played a very important role in determining their catalytic activity. The PPy films that were more rough in nature were catalytically more active than the smooth films; this may have been due to the availability of more reactive sites in the case of rough films. The apparent diffusion coefficients of the PPy film electrodes were also calculated. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: atomic force microscopy (AFM); conducting polymers; Diffusion; surface modification; Thin films